ANALISIS PRODUKSTIVITAS ALAT GALI MUAT DALAM PEMENUHAN TARGET PRODUKSI BATUBARA BULANAN DI PT PRIAMANAYA ENERGI, LAHAT SUMATERA SELATAN - Reni Arisanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Coal mining is a strategic sector that plays a vital role in meeting national energy needs and supporting the regional economy. The success of mining operations depends heavily on the company's ability to achieve production targets safely, efficiently, and sustainably. One of the main factors influencing the achievement of production targets is the productivity of mechanical equipment, particularly loading and unloading equipment. PT Priamanaya Energi, a coal mining company operating in Lahat Regency, South Sumatra, sets monthly coal production targets as the basis for planning and controlling its mining operations. This study aims to analyze the productivity of loading and unloading equipment in coal getting activities and identify factors that influence their productivity in meeting monthly production targets. The research method used is a quantitative method by processing numerical data, specifically the cycle time of the loading and unloading equipment, to calculate the actual production rate. The calculation results show that the productivity of the Caterpillar 345 Excavator loading and unloading equipment reached 239.13 tons/hour. This value has exceeded the planned production target of 200.94 tons/hour. Factors affecting loading and unloading equipment productivity include front loading conditions, weather conditions, and operator skills.Keywords: mining, productivity of loading and unloading equipment, coal, cycle time, production targets.